ANALISA PENERAPAN PENDEKATAN RULE OF REASON DALAM PUTUSAN KPPU NOMOR 04/KPPU-I/2021 TENTANG PELANGGARAN PASAL 17 UNDANG-UNDANG NOMOR 5 TAHUN 1999 DILAKUKAN PT. AERO CITRA KARGO TERKAIT JASA PENGURUSAN TRANSPORTASI EKSPOR BENIH BENING LOBSTER - Jonathan Arga Simbolon, Berry; Natasya Sirait, Ningrum; Siregar, Mahmul (Penerbit Lafadz Jaya, 2025)
Monopolistic practices arise when one or more business entities dominate the production and/or distribution of certain goods and services, resulting in unfair business competition. Article 17 of Law No. 5 of 1999 regulates monopolistic practices. The company handling the export transportation of transparent lobster seeds is called Aero Citra Kargo. It is one of the companies holding an Export Time Determination Letter, which is required for exports. In November 2020, Aero Citra Kargo became the market leader in the transportation of lobster seed exports. Aero Citra Kargo was found to have violated Article 17 in 2021. To address the Aero Citra Kargo issue, the Commission used competition law regulations, such as Government Regulation No. 44 of 2021, Competition Commission Regulation No. 1 of 2019, and Law No. 5 of 1999. By collecting secondary data encompassing primary, secondary, and tertiary legal materials, the author employed a normative literature review research method. In this case analysis, the Rule of Reason approach was applied. This method demonstrates that Aero Citra Kargo has eliminated competition in the market for export transportation services for lobster larvae in Indonesia. The Decision of the Business Competition Supervisory Commission No. 04/KPPU-I/2021 shows that Aero Citra Kargo was proven to be involved in monopolistic practices. This decision was supported by the facts of the trial and the Rule of Reason approach. Therefore, the company was not subject to fines because it did not have the ability to pay.